1998
DOI: 10.1042/bj3290131
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between transcriptional regulation by thyroid hormone and myogenin: new aspects of the Ca2+-dependent expression of the fast-type sarcoplasmic reticulum Ca2+-ATPase

Abstract: We have previously demonstrated an interaction between the major determinants of skeletal muscle phenotype by showing that continuous contractile activity represses the thyroid hormone (3,3h,5-tri-iodothyronine ; T $ )-dependent transcriptional activity of fast-type sarcoplasmic\endoplasmic-reticulum Ca# + -ATPase (SERCA1), a characteristic of the fast phenotype. Both the free cytosolic Ca# + concentration ([Ca# + ] i ) and the myogenic determination factors MyoD and myogenin have been implicated as mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Using methods of somatic gene transfer, a recent study suggested that myogenin can enhance the oxidative capacities in adult myofibres of adult animals [31]. Moreover, a moderate increase in intracellular Ca 2+ levels, as observed during tonic motor nerve activity, leads to increased myogenin levels in cultured myotubes [116]. This finding suggests a link between intracellular Ca 2+ levels, calcineurin activity and myogenin expression as previously suggested during muscle differentiation [37].…”
Section: Molecular Mechanisms Modulating Muscle Phenotype During Endumentioning
confidence: 76%
“…Using methods of somatic gene transfer, a recent study suggested that myogenin can enhance the oxidative capacities in adult myofibres of adult animals [31]. Moreover, a moderate increase in intracellular Ca 2+ levels, as observed during tonic motor nerve activity, leads to increased myogenin levels in cultured myotubes [116]. This finding suggests a link between intracellular Ca 2+ levels, calcineurin activity and myogenin expression as previously suggested during muscle differentiation [37].…”
Section: Molecular Mechanisms Modulating Muscle Phenotype During Endumentioning
confidence: 76%
“…Both cell lines did not react with a significant myotube atrophy after a 3-day treatment, and T 3 receptor analysis excluded receptor deficiency as a cause. Furthermore, in both myogenic cell lines, cross talk between T 3 -induced gene expression and contractile activity determining muscle phenotype has been reported (32,33). In both cell lines, metabolic effects of T 3 have been reported, e.g., upregulation of the sarco(endo)plasmic reticulum Ca 2ϩ -ATPases in C 2 C 12 myotubes and induction of uncoupling protein 3 in L6 myotubes (21,40).…”
Section: Discussionmentioning
confidence: 98%
“…Several lines of evidence have implicated myogenin in the fast-to-slow fiber-type shift (7,15,26,37,47). In cultured myotubes, a moderate increase in [Ca 2ϩ ] i induced a fast-to-slow fiber-type shift and enhanced the protein expression level of myogenin but not other myogenic factors (45). In the fast-twitch muscle of hypothyroid rats, shifting to a slow direction by CLFS increased the expression of myogenin with unaltered MyoD levels (37).…”
Section: Discussionmentioning
confidence: 99%